Effects of Ocean Acidification on Marine Photosynthetic Organisms Under the Concurrent Influences of Warming, UV Radiation, and Deoxygenation - Gao, Kunshan; Beardall, John; Häder, Donat-P.; Hall-Spencer, Jason M.; Gao, Guang; Hutchins, David A. (Frontiers in Marine Science, 2019)
The oceans take up over 1 million tons of anthropogenic CO2 per hour, increasing dissolved pCO2 and decreasing seawater pH in a process called ocean acidification. At the same time greenhouse warming of the surface ocean results in enhanced stratification and shoaling of upper mixed layers, exposing photosynthetic organisms dwelling here to increased visible and UV radiation as well as to a decreased nutrient supply. In addition, ocean warming and anthropogenic eutrophication reduce the concentration of dissolved O2 in seawater, contributing to the spread of hypoxic zones. All of these global changes interact to affect marine primary producers. Such interactions have been documented, but to a much smaller extent compared to the responses to each single driver. The combined effects could be synergistic, neutral or antagonistic depending on species or the physiological processes involved as well as experimental setups. For most calcifying algae, the combined impacts of acidification, solar UV and/or elevated temperature clearly reduce their calcification; for diatoms, elevated CO2 and light levels interact to enhance their growth at low, but inhibit it at high levels of sunlight. For most photosynthetic nitrogen fixers (diazotrophs), acidification associated with elevated CO2 may enhance their N2 fixation activity, but interactions with other environmental variables such as trace metal availability may neutralize or even reverse these effects. Macroalgae, on the other hand, either as juveniles or adults, appear to benefit from elevated CO2 with enhanced growth rates and tolerance to lowered pH. There has been little documentation of deoxygenation effects on primary producers, though theoretically elevated CO2 and decreased O2 concentrations could selectively enhance carboxylation over oxygenation catalyzed by Rubisco and thereby benefit autotrophs. Overall, most ocean global change biology studies have used single and/or double stressors in laboratory tests. This overview examines the combined effects of ocean acidification with other features such as warming, solar UV radiation and deoxygenation, focussing on primary producers.